Generation of neural cells using iPSCs from sleep bruxism patients with 5-HT2A polymorphism. Issue 3 (July 2017) - Hoashi, Yurie; Okamoto, Satoshi; Abe, Yuka; Matsumoto, Takashi; Tanaka, Junichi; Yoshida, Yuya; Imaizumi, Kent; Mishima, Kenji; Akamatsu, Wado; Okano, Hideyuki; Baba, Kazuyoshi
Abstract: Purpose: Sleep bruxism (SB) is classified as a sleep-related movement disorder characterized by grinding and clenching of the teeth during sleep, which is responsible for a variety of clinical problems such as abnormal tooth attrition and fracture of teeth or roots. Little is known about the etiology of SB. Our previous study identified a genomic association of the serotonin 2A receptor ( 5-HT2A ) single nucleotide polymorphism (SNP), rs6313 C > T, with SB, where the C allele carrier is associated with a 4.25-fold increased risk of SB. Based on this finding, the aim of this study was to generate of neural cells using SB patient-specific induced pluripotent stem cells (iPSCs). Methods: Two SB patients with C/C genotype of rs6313 and two controls with T/T genotype were screened by laboratory-based polysomnographic recordings and the TaqMan genotyping assay. Four lines of iPSCs, two from SB patients and two from controls, were established from peripheral blood mononuclear cells by introduction of reprogramming factors. We performed quality control assays on iPSCs using expression of markers for undifferentiated pluripotent cells, immunostaining for pluripotency markers, a three-germ layer assay, and karyotype analysis. The established iPSCs were differentiated into neurons using the neurosphere culture system. 5-HT2A gene expression in these neurons was evaluated by quantitative real-time PCR. Results: Patient-specific iPSCs were successfully differentiated into neurons expressing 5-HT2A . Conclusions: This report is the first successful generation of neural cells using iPSCs from sleep bruxism patients with 5-HT2A polymorphism, which has the potential to elucidate the etiology and underlying mechanism of SB.